БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИНИНГ МАТЕМАТИКА КОМПЕТЕНЦИЯЛАРИНИ ШАКЛЛАНТИРИШДА АХБОРОТ-КОММУНИКАЦИЯ ТЕХНОЛОГИЯЛАРИ ВОСИТАЛАРИДАН ФОЙДАЛАНИШНИНГ ПЕДАГОГИК АСОСЛАРИ - Саидова, Н.Р. (SCIENCE and SOCIETY, 2020)
The definition of the pedagogical conditions for organizing the process of using information and communication technologies in the formation of mathematical competencies of primary school students is investigated on the basis of the need to develop scientific and methodological recommendations in order to classify existing approaches, concepts, views, collection of teaching in this area and its implementation in the teacher’s activites.